2020
DOI: 10.3892/or.2020.7473
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces re‑expression of BRCA1 and suppression of γ synuclein by modulating DNA promoter methylation in breast cancer cell lines

Abstract: Restoration of normal DNA promoter methylation and expression states of cancer-related genes may be an option for the prevention as well as the treatment of several types of cancer. Constitutional promoter methylation of BRCA1 DNA repair associated (BRCA1) gene is linked with a high risk of developing breast and ovarian cancer. Furthermore, hypomethylation of the proto-oncogene γ synuclein (SNCG) is associated with the metastasis of breast and ovarian cancer and reduced disease-free survival (DFS). In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 48 publications
(68 reference statements)
2
30
0
Order By: Relevance
“…The same effect on DNMT1 was reported in curcumintreated breast cancer cells, but the effects were different between cell lines. For example, in HCC-38 cells, the curcumin-dependent decrease in DNMT1 together with the inhibition of miR-29b caused an increase in TET1 (a methylcytosine dioxygenase that plays an important role in the demethylation of DNA) allowing BRCA1 re-expression, but this did not occur in T47D cells (40). It is also important to note that the response to DNA damage triggered by curcumin and varies according to the BRCA1 mutation status in triple negative breast cancer cells, but regardless of this, in all cases it leads to apoptosis (41).…”
Section: Curcuminmentioning
confidence: 99%
“…The same effect on DNMT1 was reported in curcumintreated breast cancer cells, but the effects were different between cell lines. For example, in HCC-38 cells, the curcumin-dependent decrease in DNMT1 together with the inhibition of miR-29b caused an increase in TET1 (a methylcytosine dioxygenase that plays an important role in the demethylation of DNA) allowing BRCA1 re-expression, but this did not occur in T47D cells (40). It is also important to note that the response to DNA damage triggered by curcumin and varies according to the BRCA1 mutation status in triple negative breast cancer cells, but regardless of this, in all cases it leads to apoptosis (41).…”
Section: Curcuminmentioning
confidence: 99%
“…Accumulating evidence indicates that the human diet is a source of micronutrients (folate, B vitamins, betaine, choline, and methionine; Figure 2 ) and bioactive compounds (curcumin, epigallocatechin-3-gallate, genistein, quercetin, resveratrol, and sulforaphane; Figure 2 ) that act as both chemopreventative and chemotherapeutic agents by modulating the epigenome [ 13 , 14 , 15 , 16 , 18 ].…”
Section: The Effect Of Natural Dietary Micronutrients and Bioactivmentioning
confidence: 99%
“…Despite this, the exact mechanism by which these compounds prevent and inhibit carcinogenesis remains unclear. Emerging evidence suggests that dietary micronutrients and bioactive molecules exhibit anti-cancer properties by reversing abnormal gene activation and inhibition through epigenetic modifications such as DNA methylation [ 13 , 14 , 15 , 16 , 17 , 18 ], and these changes in DNA methylation may provide insight into future therapeutic interventions. In this review, we summarize existing literature on natural dietary micronutrients, bioactive compounds, and food-borne mycotoxins that affect DNA methylation patterns and identify its potential in the onset and treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to resveratrol, curcumin was found to stimulate β-oxidation of fatty acids, inhibiting adipogenesis, and inflammation ( 90 ). Al-Yousef et al ( 91 ) recently reported that curcumin treatment restored BRCA1 expression through reduction of its promoter methylation level in TNBC cell lines HCC-38 and UACC-3199. Lower levels of BRCA1 promoter methylation were attributed to upregulation of the ten-eleven translocation 1 (TET1) gene, which mediates DNA demethylation via hydroxylation of 5-methylcytosine to 5-hydroxymethylcytosine.…”
Section: Bioactive Food Componentsmentioning
confidence: 99%